2022
DOI: 10.3390/polym14071305
|View full text |Cite
|
Sign up to set email alerts
|

Yellowing, Weathering and Degradation of Marine Pellets and Their Influence on the Adsorption of Chemical Pollutants

Abstract: Marine microplastics (MPs) are exposed to environmental factors, which produce aging, weathering, surface cracking, yellowing, fragmentation and degradation, thereby changing the structure and behavior of the plastic. This degradation also has an influence on the adsorption of persistent organic pollutants over the microplastic surface, leading to increased concentration with aging. The degradation state affects the microplastic color over time; this is called yellowing, which can be quantified using the Yello… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Aged pellets are easy to identify as they have turned from white to yellow. 36 This change in yellowing index becomes more pronounced with age and weathering. 36 Hence, this simple technique is used to sort the pellets based on their age, provided the changes in the yellowing index are substantial.…”
Section: Pellets Selection and Microplastics Productionmentioning
confidence: 95%
See 3 more Smart Citations
“…Aged pellets are easy to identify as they have turned from white to yellow. 36 This change in yellowing index becomes more pronounced with age and weathering. 36 Hence, this simple technique is used to sort the pellets based on their age, provided the changes in the yellowing index are substantial.…”
Section: Pellets Selection and Microplastics Productionmentioning
confidence: 95%
“…36 This change in yellowing index becomes more pronounced with age and weathering. 36 Hence, this simple technique is used to sort the pellets based on their age, provided the changes in the yellowing index are substantial. 36 Otherwise, combining the yellowing index with Fouriertransform infrared microscopy is required, which is not necessary here because we consider only groups of pellets that present a consequent change in the yellowing index.…”
Section: Pellets Selection and Microplastics Productionmentioning
confidence: 95%
See 2 more Smart Citations
“…Abaroa et al [82] showed an increase in adsorption with aging, and proposed that the use of an indicator, the yellowness index (YI), related to the color change that microplastics present over time. This YI is estimated visually based on the color of the MPs and is related to the speed at which the POPs are adsorbed on the particles.…”
Section: Effect Of Agingmentioning
confidence: 99%